Symptom prevalence in patients with advanced skin cancer. Issue 2 (23rd July 2016) - Goto, Hiroyuki; Yoshikawa, Shusuke; Otsuka, Masaki; Omodaka, Toshikazu; Yoshimi, Kosuke; Yoshida, Yuichi; Yamamoto, Osamu; Kiyohara, Yoshio
Abstract: Knowledge of the prevalence of symptoms in patients with incurable cancer in the terminal stage is important for clinicians. However, there has been no report on the prevalence of symptoms in patients with incurable skin cancer. We analyzed the prevalence of symptoms in 224 patients who died due to skin cancer in our center. These data were obtained from medical records compiled by a miscellaneous population of medical staff retrospectively. We evaluated the symptoms at 3 months, 1 month, 2 weeks, 1 week and 3 days before the patients died. Data for symptoms included Eastern Cooperative Oncology Group performance status and the presence or absence of the following 13 symptoms: (i) bleeding or exudate; (ii) pain or necessity for an analgesic; (iii) fatigue; (iv) anorexia; (v) nausea; (vi) dyspnea or need for oxygen administration; (vii) bloating; (viii) insomnia; (ix) delirium; (x) drowsiness; (xi) anemia; (xii) spasm; and (xiii) paralysis. The average performance status gradually progressed. Pain and anorexia were the most common symptoms in patients with advanced skin cancer. Dyspnea, anemia and drowsiness also tended to be frequent as death approached despite the fact that the frequencies of these symptoms were not high 3 months before death. We considered that frequencies of prevalence of pain and dyspnea were due to bone and lung metastases. Bleeding or exudate from lesions is a characteristic symptom in patients with skin cancer. Our results regarding the prevalence of symptoms in patients with advanced skin cancer will be helpful for medical professionals to assess patients' conditions and to plan treatment.